2020
DOI: 10.1175/jas-d-20-0059.1
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Upper-Level Coupling on Great Plains Low-Level Jet Structure and Variability

Abstract: The Great Plains (GP) southerly nocturnal low-level jet (GPLLJ) is a dominant contributor to the region’s warm season (May–September) mean and extreme precipitation, wind energy generation and severe weather outbreaks—including mesoscale convective systems. The spatiotemporal structure, variability, and impact of individual GPLLJ events are closely related to their degree of upper-level synoptic coupling, which varies from strong coupling in synoptic trough/ridge environments to weak coupling in quiescent, syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(25 citation statements)
references
References 56 publications
2
21
2
Order By: Relevance
“…At decadal-to-multidecadal timescales, jet variability has been linked to atmospheric conditions in the North Pacific as indexed by the PDO, especially during May (Agrawal et al, 2021). The analysis was designed to complement Burrows et al (2020) but by adopting its Eulerian perspective inherited certain limitations. Fixed domains of comparison (i.e., NGP, CGP, and SGP) preclude the detection of shifts in the GPLLJ corridor, including a potential shift of the GPLLJ exit northward since 1979 as documented by Barandiaran et al (2013).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…At decadal-to-multidecadal timescales, jet variability has been linked to atmospheric conditions in the North Pacific as indexed by the PDO, especially during May (Agrawal et al, 2021). The analysis was designed to complement Burrows et al (2020) but by adopting its Eulerian perspective inherited certain limitations. Fixed domains of comparison (i.e., NGP, CGP, and SGP) preclude the detection of shifts in the GPLLJ corridor, including a potential shift of the GPLLJ exit northward since 1979 as documented by Barandiaran et al (2013).…”
Section: Discussionmentioning
confidence: 99%
“…850-hPa ageostrophic wind is approximately the same for both jet classes in the NGP, however, uncoupled jets have moderately faster 850-hPa ageostrophic winds over the CGP and SGP (Figure 7). Campbell et al (2019) also found that drier land surfaces associated with uncoupled jets (i.e., Burrows et al, 2020; their Figure S5) act to enhance ageostrophic winds.…”
Section: Climatological Jet Type Differencesmentioning
confidence: 92%
See 3 more Smart Citations